Empowering young people through participatory film: a postmethodological approach. Issue 8 (11th June 2017) - Canosa, Antonia; Wilson, Erica; Graham, Anne
Abstract : Children and young people's voices have often been neglected in tourism research, and this is particularly the case when exploring tourism from the host community's perspective. The lack of children and young people in tourism research has been attributed to the slow engagement and adoption of alternative and critical methodologies which open up new and fresh ways of interpreting reality. The paper aims to explore the potential for participatory film to uncover the perspectives of marginalised members of the community such as children and young people. We also discuss the use of participatory film as an epistemic philosophy, and as a post-disciplinary form of methodology (or 'postmethodology') which is ideologically grounded. The findings suggest that children and young people feel strongly about their community and display feelings of anger and frustration towards tourists who are perceived to not respect the community and the environment. The methodological contribution of this paper lies in the use of an innovative and voice-generative participatory visual method to empower young people to actively participate in tourism research.